Effect of Ultrasound and Cellulase Pre-Treatment on Extractability and Properties of Taro Starch - Sit, Nandan (JOURNAL OF ROOT CROPS, 2017)
Ultrasound and cellulase pre-treatment was applied for the extraction of starch from taro tubers and their effect on yield and properties of the extracted starch was studied. Ultrasonication time was varied at three levels of 0, 10 and 20 min whereas cellulase concentration was varied at two levels of 0 and 200 U/100 g tuber. It was observed that higher yield was obtained with ultrasonication as well as cellulase treatment. When both the treatments were combined, yield achieved was much higher compared to conventional extraction. Highest yield of 19.36% was obtained when ultrasonication was carried out for 20 min and was then treated with cellulase at concentration of 200 U/100 g tubers. The functional properties was comparable to conventionally extracted starch when cellulase treatment alone was carried out. The swelling and solubility increased with ultrasonication and was time dependent. Clarity of the starch pastes improved with cellulase treatment and was negatively affected by ultrasonication. Maximum clarity was observed for starch extracted by cellulase treatment only. Freeze-thaw stability of the starch pastes improved for ultrasonically extracted starch and was not affected by cellulase treatment. Pasting properties were not much affected by ultrasonication for 10 min and cellulase treatment, but when ultrasonication time was increased to 20 min, the peak and final viscosities were found to be significantly increased. Higher yield of starch with better properties like improved freeze-thaw stability, high paste viscosity and swelling and better clarity can be obtained from taro tubers by combined pre- treatment with ultrasound and cellulase, which will help in the commercial exploitation of this underutilized tuber.